2014
DOI: 10.1097/mib.0000000000000175
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Heat Shock Protein gp96 Ameliorates CD4+CD62L+ T-Cell–mediated Transfer Colitis

Abstract: These findings indicate an essential role of gp96 in the maintenance of tolerance against luminal antigens in the intestinal mucosa. The absence of gp96 in intestinal macrophages of patients with Crohn's disease might provoke loss of this tolerance mediating mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…This theory is supported by the fact that gp96 is induced during differentiation of normal intestinal macrophages, but not detected in intestinal macrophages in the gut mucosa of CD patients [134]. As gp96 may have a role in tolerance induction, this observation suggests that downregulation of gp96 is responsible for the loss of tolerance against luminal bacteria found in CD patients [134, 135]. …”
Section: Role Of Gp96 In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…This theory is supported by the fact that gp96 is induced during differentiation of normal intestinal macrophages, but not detected in intestinal macrophages in the gut mucosa of CD patients [134]. As gp96 may have a role in tolerance induction, this observation suggests that downregulation of gp96 is responsible for the loss of tolerance against luminal bacteria found in CD patients [134, 135]. …”
Section: Role Of Gp96 In Cancermentioning
confidence: 99%
“…They further demonstrated that immunization with high doses of gp96 can prevent myelin basic protein- or proteolipid protein-induced autoimmune encephalomyelitis in SJL mice and the onset of diabetes in non-obese diabetic (NOD) mice [148]. Similar protective effects were implicated in T cell-mediated immune disorders including IBD [135] and liver injury [149]. These studies indicated that gp96 plays different immune regulatory roles in a dose-dependent manner.…”
Section: T Cell Intrinsic Gp96: Implications For Cellular Therapymentioning
confidence: 99%